Sex differences and normative data for the m-CTSIB and sensory integration on baseline concussion assessment in collegiate athletes. (2nd January 2020) - Moran, Ryan N.; Meek, Jeff; Allen, Jeff; Robinson, James
ABSTRACT: Primary objective : To investigate sex differences on baseline m-CTSIB and sensory integration function between male and female collegiate athletes and develop preliminary normative data for this population. Methods and procedures : Baseline data were retrospectively analyzed for 591 National Collegiate Athletic Association (NCAA) athletes between 2015 and 2018 on the modified Clinical Test for Sensory Interaction and Balance (m-CTSIB). A series of Mann–Whitney U tests were conducted to determine sex differences on m-CTSIB and individual sensory integration performance. Main outcomes and results : Female athletes performed significantly better than male athletes on baseline m-CTSIB composite scores ( p < .001). Females also performed better on the eyes open-firm surface ( p < .001), eyes closed-firm surface ( p = .001), eyes open-foam surface ( p < .001), and eyes closed-foam surface ( p = .001) tasks as compared to male athletes. Conclusions : Male and female athletes exhibit differences on baseline m-CTSIB and sensory integration test performance. The m-CTSIB normative data are presented for the total sample and by sex. These normative data provide a frame of reference for interpreting m-CTSIB performance in collegiate athletes as part of concussion assessment.